2021
DOI: 10.1002/srin.202100198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yttrium on the Microstructure and Properties of 20MnSi Steel

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/srin.202100198.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…[ 32 ] In this study, from Figure 7 and 8, it can be found that the RE‐containing inclusion does not changes the element distribution in the nearby matrix to facilitate ferrite or cementite phase transformation. Zhong et al, [ 33 ] Shim et al, [ 34 ] and Qi et al [ 35 ] found Y‐containing inclusions assist ferrite nucleation by heterogeneous nucleation. Therefore, it is reasonable to think that the small‐sized RE‐containing inclusions in the investigated steel provide low‐energy nucleus/inclusion interfaces to stimulate the heterogeneous nucleation for pearlite phase transformation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ] In this study, from Figure 7 and 8, it can be found that the RE‐containing inclusion does not changes the element distribution in the nearby matrix to facilitate ferrite or cementite phase transformation. Zhong et al, [ 33 ] Shim et al, [ 34 ] and Qi et al [ 35 ] found Y‐containing inclusions assist ferrite nucleation by heterogeneous nucleation. Therefore, it is reasonable to think that the small‐sized RE‐containing inclusions in the investigated steel provide low‐energy nucleus/inclusion interfaces to stimulate the heterogeneous nucleation for pearlite phase transformation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the addition of elements such as Cr, Mo, and Ni can improve the steel microstructure and increase the stability of passivation films, thus enhancing the corrosion resistance of the steel. [6][7][8] It has been proven that rare earth (RE) elements can significantly improve the cleanliness [9] and microstructure [10] of steel. For example, Liu et al [11] reported that by adding 0.022 wt% of RE to 718 steel, the O content was reduced from 15 ppm to 6 ppm, and the inclusions were changed from MnS and Al 2 O 3 to RE 2 O 3 , RES, RE 2 O 2 S, and REAlO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that rare earth (RE) elements can significantly improve the cleanliness [ 9 ] and microstructure [ 10 ] of steel. For example, Liu et al [ 11 ] reported that by adding 0.022 wt% of RE to 718 steel, the O content was reduced from 15 ppm to 6 ppm, and the inclusions were changed from MnS and Al 2 O 3 to RE 2 O 3 , RES, RE 2 O 2 S, and REAlO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 12–17 ] Besides, the microstructure and property of steels could be significantly improved by an appropriate addition of rare earth elements. [ 18–23 ] Li et al [ 24 ] found that the evolution path of a Si‐Al killed 253 MA steel was Si–Al–O→Ce 2 O 3 (Ce 2 O 2 S) →Ce–Si–Al–O, which was in liquid state under 1773 K. Ren et al [ 25 ] found that when the cerium content in an aluminum‐killed steel increased from 0 to 280 ppm, the modification sequence of inclusions was Al 2 O 3 → CeAlO 3 → Ce 2 O 2 S → Ce 2 O 2 S and CeS. Li et al [ 26 ] found that the undercooling degree of a 1045 steel could be reduced by cerium‐containing inclusions, and the equiaxed grain zone in the cast steel was enlarged after additions of rare earth elements.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Besides, the microstructure and property of steels could be significantly improved by an appropriate addition of rare earth elements. [18][19][20][21][22][23] Li et al [24] found that the evolution path of a Si-Al killed 253 MA steel was Si-Al-O!Ce 2 O 3 (Ce 2 O 2 S) !Ce-Si-Al-O, which was in liquid state under 1773 K. Ren et al [25] found that when the cerium content in an aluminum-killed steel increased from 0 to 280 ppm, the modification sequence of inclusions was Al 2 O 3 ! CeAlO 3 !…”
mentioning
confidence: 99%